Culture-specificity of teacher demotivation: Iranian junior high school teachers caught in the newly-introduced CLT trap!. Issue 2 (17th February 2017) - Yaghoubinejad, Hadi; Zarrinabadi, Nourollah; Nejadansari, Dariush
Abstract: Research has shown that lack of motivation on either students or teachers' part negatively influences language learning. The latter case is a serious problem in this regard, since an unmotivated teacher will extinguish his learners' enthusiasm and energy for learning. This study employed a mixed-method approach to investigate the demotivating factors for Iranian junior high school teachers. For the quantitative stage of the study, a questionnaire on demotivation was distributed among 105 participant teachers to find out the dominant demotivating factors. In the qualitative stage, and in order to gain a better picture of the salient demotivating factors and the reasons behind them, a set of semi-structured interviews with 10 volunteer teachers were conducted. The results indicated that lack of social recognition and respect, few adequate rewards, lack of supports or understanding regarding English education, and a large number of students in a single English class were the major demotivating factors for Iranian teachers. In the interviews, it was found that the participants perceived the first two items as specific to Iranian educational context. Finally, the implications for policy-makers and material developers and suggestions for future researchers are discussed.